2019
DOI: 10.1186/s12960-019-0424-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Everything was just getting worse and worse’: deteriorating job quality as a driver of doctor emigration from Ireland

Abstract: BackgroundMedicine is a high-status, high-skill occupation which has traditionally provided access to good quality jobs and relatively high salaries. In Ireland, historic underfunding combined with austerity-related cutbacks has negatively impacted job quality to the extent that hospital medical jobs have begun to resemble extreme jobs. Extreme jobs combine components of a good quality job—high pay, high job control, challenging demands, with those of a low-quality job—long working hours, heavy workloads. Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…3 The VA hospital system in Los Angeles made their PPE equipment economic appeal of reducing worker protections and privatizing public goods like health care has made inroads in other countries. Macklin and Spurgin's argument about employee speech limitations in Australia notes recent acts that have reduced employee rights [2007], and of course austerity practices in many European countries have in some instances led to employees' perception of lack of autonomy at work [see Humphries et al, 2019].…”
Section: Ppe Shortages and Employee Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The VA hospital system in Los Angeles made their PPE equipment economic appeal of reducing worker protections and privatizing public goods like health care has made inroads in other countries. Macklin and Spurgin's argument about employee speech limitations in Australia notes recent acts that have reduced employee rights [2007], and of course austerity practices in many European countries have in some instances led to employees' perception of lack of autonomy at work [see Humphries et al, 2019].…”
Section: Ppe Shortages and Employee Silencingmentioning
confidence: 99%
“…2 While Hirschman's text is 50 years old, it has continually been applied and extended to analyses of worker rights and voice. For recent examples, see for instance Stoker [2005], Chen and Lai [2014], Hoffmann [2006], Humphries et al [2019] and MacGregor and Stuebs [2014].…”
Section: Ppe Shortages and Employee Silencingmentioning
confidence: 99%
“… 1–3 Austerity measures introduced following the 2008 global financial crisis reduced health spending, 1 staffing levels, hospital bed numbers 4 and new entrant salaries. One study of Irish-trained doctors who emigrated to Australia between 2008 and 2018 found that they did so in response to deteriorating working conditions 5 in the Irish health system. Moving to Australia, which had escaped the worst effects of the global financial crisis, 1 enabled these doctors to access better working conditions and a better work–life balance.…”
Section: Introductionmentioning
confidence: 99%
“…Moving to Australia, which had escaped the worst effects of the global financial crisis, 1 enabled these doctors to access better working conditions and a better work–life balance. 5 …”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with, for example, the NHS, where most junior doctors work in shift patterns. There is a significant issue with retention of doctors in Ireland, the normalization of extreme working hours identified as a key driver of doctor emigration and a key deterrent of repatriation [12,13] has been implicated as a cause for significant issues with retention of doctors in Ireland [14].…”
Section: Introductionmentioning
confidence: 99%